STATEMENT OF OPTIMAL SYNTHESIS PROBLEM FOR AUTONOMOUS HIGH-ACCURACY RESISTANT TO DISTURBANCE STABILIZATION AND COURSE SYSTEM - Sushchenko, Olga A.; Lutzko, Dmitro O. (Proceedings of National Aviation University (archive), 2010)
Approaches to statement of the optimal synthesis problem for the control systems of the wide kind vehicle are analysed and the formalized statement of the optimal synthesis problem for autonomous high-accuracy resistant to disturbance stabilization and course system is formulated. The optimum criterion for the formulated problem is defined. The structural and non-structural uncertainties of the stabilization systems are analysed.